ROLE OF LEKHAN BASTI IN MEDOROGA- A CASE REPORT - Watkar Deepali Prakash; Gahukar Dhanraj (International Journal of Applied Ayurved Research, 2019)
Sthaulya is an alarming health problem of modern society. It is a predominant metabolic disorder and described by Acharya Charak in Ashtaunindita Purusha. Many theory and medicament put toward us for the management of the disease but till now perfect remedy for this problem is not found in modern medicine also so people are expecting solution from ayurveda. It is mentioned among santarpana janita vyadhi in ayurvedic text. In sthaulya etiological factors mainly vitiate Meda-Kapha and Vata get avarita by excessive Meda. Thus if we used only aptarpaka Dravya, it increases the vitiated vata. Therefore treatment should be planed considering vitiated vata, meda and kapha. Panchakarma is the prime tool of Ayurvedic therapies. It mainly consider as Shodhana therapy. Acharya Charaka quoted that there is a chance of recurrence in disease treated by shaman therapy but Shodhana therapy cures the disease from its root and there is no chance of recurrence. Myocardial infarction ischemic heart diseases, atherosclerosis, hypertention, diabetes, osteoarthritis, impotency and mental disorder are some of the complication which are seen to have serious effect on the disease itself. Several studies were done in ayurveda and modern medicine. For the control of obesity (Sthoulyaroga). In ayurveda lekhan basti has a very important role to play in management of sthoulyaroga.